2014
DOI: 10.1016/j.foodpol.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Can consumers’ willingness to pay incentivize adoption of environmental impact reducing technologies in meat animal production?

Abstract: a b s t r a c tThis study develops a model estimating consumer willingness to pay (WTP) for environmental meat attributes and uses a multi-objective nutritional optimizer to explore the extent to which WTP can offset on-farm costs of reducing water use. Data for the WTP model are sourced from a literature survey of the Agricola and Google Scholar databases yielding 46 studies estimating WTP for pure and impure (organic, grass-fed, natural) environmental meat attributes. Bayesian analysis is used to estimate 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This produced a list of 138 studies reporting WTP. Some studies were excluded, of which 13 were qualitative and quantitative review (e.g., Anselmsson et al ., ; Cicia and Colantuoni, ; Lagerkvist and Hess, ; Deselnicu et al ., ; Tully and Winer, ; White and Brady, ), 15 were about other food products, such as chicken and fruits, and wood products (e.g., Aguilar and Vlosky, ; Janssen and Hamm, ; Campbell and Doherty, ), and 16 expressed WTP as awareness scores or a probability of WTP rather than monetary measurements. Therefore, 94 studies with 566 observations were produced for our meta‐analysis.…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This produced a list of 138 studies reporting WTP. Some studies were excluded, of which 13 were qualitative and quantitative review (e.g., Anselmsson et al ., ; Cicia and Colantuoni, ; Lagerkvist and Hess, ; Deselnicu et al ., ; Tully and Winer, ; White and Brady, ), 15 were about other food products, such as chicken and fruits, and wood products (e.g., Aguilar and Vlosky, ; Janssen and Hamm, ; Campbell and Doherty, ), and 16 expressed WTP as awareness scores or a probability of WTP rather than monetary measurements. Therefore, 94 studies with 566 observations were produced for our meta‐analysis.…”
Section: Methods and Datamentioning
confidence: 99%
“…The percentage premium was measured by the percentage change in WTP from a base price for the CAs, which allows us to quantify the increased monetary value that consumers place on CAs . This method of measurement has been commonly used in WTP meta‐analysis studies (e.g., Cicia and Colantuoni, ; Tully and Winer, ; White and Brady, ; Del Giudice et al ., ). In many cases, studies presented dollar value estimates of WTP premiums and a base price was sourced from the text.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also found consumers willing to pay premiums for meat produced with reduced environmental impacts (Hurley, Miller, and Kliebenstein, 2006; Tonsor and Shupp, 2009). In a meta-analysis on estimates of consumer WTP for environmental impact–reducing technologies in meat production, White and Brady (2014) found that consumers would pay a 29% premium for environmental attributes (local, all natural, grass fed, organic) that had both public and egocentric benefits, versus a 14.8% premium for purely public benefits (e.g., GHG reductions).…”
Section: Introductionmentioning
confidence: 99%
“…The theory of impure public goods views VEPs, particularly eco-labeling, as a way for firms to profit by providing the market with bundles of environmentally friendly goods to satisfy consumers' demands for products and for the health of the environment. Experimental willingness to pay estimates associated with ecolabeling in meat production range from a 5 percent to a 15 percent premium (Dransfield, et al, 2005;White & Brady, 2014;Lusk, et al, 2006).…”
Section: The Theory Behind Vepsmentioning
confidence: 99%